Civic education in South-Eastern Europe: Education and training for human rights and active democratic citizenship - Spajić-Vrkaš, Vedrana (Array, 2012)
The paper describes the context, the conceptual and methodological framework and the results of the pilot-study conducted in seven countries of the South-Eastern Europe (Albania, Croatia, Bosnia and Herzegovina, Montenegro, Romania, Serbia and Slovenia) Europe during 2009 among the students in their last year of secondary school. The project was coordinated by the CIVITAS BiH in cooperation with the RTC for Human Rights and Democratic Citizenship of the Faculty of Humanities and Social Studies of the University of Zagreb. The research focused on three areas: students' civic and political knowledge, their attitudes towards human rights and citizenship education instruction in schools and their civic and political culture. The results displayed similarities and differences in all three areas among the countries. The most interesting result is, however, that, generally speaking, the schools across the region are still more focused on enhancing a duty-based citizenship instead on strengthening an emancipated and engaged citizenship.